Slow-Wave Half-Mode Substrate Integrated Waveguide Using Spoof Surface Plasmon Polariton Structure - Guan, Dong-Fang; You, Peng; Zhang, Qingfeng; Yang, Zhang-Biao; Liu, Haiwen; Yong, Shao-Wei (IEEE transactions on microwave theory and techniques, 2018)
In this paper, we propose a novel slow-wave half-mode substrate integrated waveguide (HMSIW) combined with spoof surface plasmon polariton (SPP) structure. In this design, subwavelength corrugated grooves are etched on the up metal layer of HMSIW to support an SPP mode. The dispersion and transmission characteristics of the proposed hybrid HMSIW-SPP structure are analyzed and compared with the classic HMSIW. To experimentally validate this design, a prototype is fabricated and measured. A slow-wave effect is clearly observed in the proposed hybrid transmission line, and its wavelength is reduced by over 50% without sacrificing its transmission performance. This structure features a simple architecture and excellent slow-wave effect.